UPAYA PENINGKATAN PROMOSI OBJEK WISATA BONO DI TELUK MERANTI KABUPATEN PELALAWAN - Nadya Harlyn; Achmad Hidir (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study aimed to obtain data and information on: (1) Improving the Promotion attractions Bono in Teluk Meranti Pelalawan Riau (2) Obstacles encountered by the Government to meningkatkankan promotion of attractions Bono in Teluk Meranti Pelalawan Riau (3) Strategy undertaken by the government to improve the promotion of attractions Bono in Teluk Meranti PelalawanThis type of research is descriptive qualitative using interviews, observation and research directly spaciousness. Furthermore, the data collected through the interview,observation, after the research data obtained then the data were analyzed through imaging techniques with the words.The results of research in the field as follows: a) Promotional Efforts made by the government Specifically the Department of Culture, Tourism, Youth and Sports Namely Through Advertising, Sales Promotion, Personal Selling, Direct Marketing and quite good. b) Obstacles encountered Improving the Government in the promotion Barriers attractions Bono among others: Lack of Facilities and Infrastructure, yet Optimally promotion and marketing program, not yet optimal preservation Development and Management attractions Bono. c) Strategies undertaken by the government in improving the Promotion attractions Bono namely: Utilizing a variety of means of information media as a way to promote the attraction bono to the local tourist and International, Improving the quality of facilities and infrastructures in tourist sites, Cooperating with the tourism businessmen or investors according to their respective fields.Key Word: Bono Attractions, Promotion, Strategy